Blood draw site and blood matrix influence mineral assessment - Mikail G. Alejandro; Kathleen Schultz; David W. Killilea (PLoS ONE, 2025)
Circulating mineral concentrations are used to assess nutritional status or as markers for clinical conditions, but the quality of these measurements depends on the methods used for blood processing. Since the procedures for measuring mineral levels in blood are not standardized, discrepancies in sampling may influence the analytical results. We previously reported that zinc content in blood samples showed significant variation depending on several pre-analytical variables selected during blood collection and processing. In this study, we extend our analysis to determine how other mineral levels might be affected by different blood draw sites (capillary or venous) or sample matrices (plasma or serum). Sequential capillary and venous blood samples were collected from a diverse cohort of sixty healthy adults and analyzed for multiple minerals using inductively coupled plasma–optical emission spectrometry. Calcium, copper, iron, and magnesium were the only minerals that were detected in all samples and were free from contamination in the blood collection tubes used for the study. When assessing different blood draw sites, the concentrations of calcium, copper, iron, and magnesium were 2–11% higher from capillary compared to the venous plasma. When assessing different blood sample matrices, the concentrations of calcium, copper, and magnesium were 2–5% higher in serum compared to plasma samples, whereas the concentration of iron was 7% higher in plasma compared to serum samples. The differences observed in these four essential minerals from discrepant draw sites and blood matrices demonstrate the importance of controlling key pre-analytic variables when assessing mineral levels in blood.